2003
DOI: 10.1038/sj.cdd.4401272
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced apoptosis is impaired in cells with a lysosomal targeting defect but is not affected in cells synthesizing a catalytically inactive cathepsin D

Abstract: The role of cathepsin D in stress-induced cell death has been investigated by using ovine fibroblasts exhibiting a missense mutation in the active site of cathepsin D. The cathepsin D (lysosomal aspartic protease) deficiency did not protect cells against toxicity induced by doxorubicin and other cytotoxic agents, neither did it protect cells from caspase activation. Moreover, the cathepsin D inhibitor, pepstatin A, did not prevent stress-induced cell death in human fibroblasts or lymphoblasts. The possible rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…Altogether, these findings suggest that stress-induced ceramide generation precedes activation of the lysosomal pathway, in agreement with our previous study (53). However, further investigations are needed to clarify how, where, and with which proteases the ceramide pathway is connected with the lysosome in TNFinduced apoptosis.…”
Section: Figsupporting
confidence: 92%
See 3 more Smart Citations
“…Altogether, these findings suggest that stress-induced ceramide generation precedes activation of the lysosomal pathway, in agreement with our previous study (53). However, further investigations are needed to clarify how, where, and with which proteases the ceramide pathway is connected with the lysosome in TNFinduced apoptosis.…”
Section: Figsupporting
confidence: 92%
“…Previous studies showed that pepstatin A, an aspartic protease inhibitor, did not inhibit TNF-induced cell death (53). As shown in Fig.…”
Section: Effect Of Cathepsin Inhibitors On Tnf-induced Cell Death In mentioning
confidence: 66%
See 2 more Smart Citations
“…These data suggests that CD promote apoptosis induced by cytotoxic and stress agents. It should be noted, however, that the central role of CD in induced apoptosis has been challenged by other reports [128,129]. Moreover, anti-apoptotic role of CD has been also described.…”
Section: Apoptosismentioning
confidence: 92%